Experimental and Numerical Study on the Influence of Corrosion Rate and Shear Span Ratio on Reinforced Concrete Beam - Xiao Guo; Hongwei Wang; Kaizhong Xie; Tuo Shi; Dan Yu (Advances in Materials Science and Engineering)
In order to study the influence of corrosion rate and shear span ratio on reinforced concrete beam, a numerical analysis method of corroded reinforced concrete beam was put forward. Bond-slip relationship formula between reinforcement and concrete was suggested. A three-dimensional finite element model of corroded reinforced concrete beam was established. Calculation method of ultimate bearing capacity for reinforced concrete beam was suggested. Ultimate bearing capacity experiment on 14 corroded reinforced concrete beams with different corrosion rates and shear span ratios was carried out. Numerical analysis results and experimental results were compared and analyzed. The results show that, for reinforced concrete beams with different corrosion rates and shear span ratios, load-deflection curve can be divided into elasticity stage and plasticity stage. With the increase of corrosion rate and shear span ratio, ultimate bearing capacity of corroded reinforced concrete beam decreased. When shear span ratio was 3.0, if corrosion rate increased by 1%, experimental value of ultimate bearing capacity decreased by 1.002 kN. When shear span ratio was 2.4, if corrosion rate increased by 1%, experimental value of ultimate bearing capacity decreased by 1.849 kN. The numerical analysis method put forward in this paper was feasible, and the suggested ultimate bearing capacity calculation method for reinforced concrete beam has a high accuracy.